EFFECT OF VERMICOMPOST ON THE GROWTH AND YIELD OF SPRING ONION (ALLIUM FISTULOSUM L.) - Luu, Hai Thi Thuy; Le, Linh Truc; Green, Iain D. (Journal of Agricultural Sciences (Belgrade), 2024)
Spring onions (Allium fistulosum L.) are a popular salad vegetable produced widely over the world, including in Vietnam. Thanks to their flavor and aroma, they are an indispensable ingredient used to flavor soup and other dishes. Vermicompost is a natural and environmentally friendly fertilizer used widely to increase crop production and maintain the sustainability of agrosystems. Consequently, this present study was conducted to investigate the efficiency of vermicompost at different application rates in promoting the growth and yield parameters of spring onions. The results showed that adding vermicompost to spring onion production had significant positive effects on plant height, number of leaves, number of tillers, individual weight, and plot yield. Particularly, the application of vermicompost at 40 t ha-1 showed the highest performance in observed parameters, increasing the number of leaves, number of tillers, individual plant weight, and plot yields to 64.78, 21.18, 302.96 g plant-1, and 4.86 kg m-2, respectively. Plot yield in the treatments of the highest and lowest vermicompost application increased by 49.1% and 3.9%, respectively, in comparison to the control. Consequently, a strongly positive relationship between the application rate of vermicompost and the plot yield was shown.